2014
DOI: 10.1086/675837
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Surveillance: Surgical Site Infections Excluded by the January 2013 Updated Surveillance Definitions

Abstract: The updated 2013 Centers for Disease Control and Prevention/ National Healthcare Safety Network definitions for surgical site infections (SSIs) reduced the duration of prolonged surveillance from 1 year to 90 days and defined which procedure types require prolonged surveillance. Applying the updated 2013 SSI definitions to cases analyzed using the pre-2013 surveillance definitions excluded 10% of previously identified SSIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…After 90 days, only a few more SSIs were detected, triggering discussion about whether those late SSIs are truly due to preventable issues during the operation [16]. Three of the five studies mentioned [15][16][17] confirm our finding that more SSIs are missed after knee-replacement surgery than after hip replacement surgery when the follow-up is reduced to 90 days.…”
Section: Comparison With Literaturesupporting
confidence: 70%
See 3 more Smart Citations
“…After 90 days, only a few more SSIs were detected, triggering discussion about whether those late SSIs are truly due to preventable issues during the operation [16]. Three of the five studies mentioned [15][16][17] confirm our finding that more SSIs are missed after knee-replacement surgery than after hip replacement surgery when the follow-up is reduced to 90 days.…”
Section: Comparison With Literaturesupporting
confidence: 70%
“…To the best of our knowledge, no European studies and only a few American and Canadian studies have analysed timing of SSIs to quantify the impact of a shorter PDS duration [10,[15][16][17][18]. None of these studies used survival techniques to visually demonstrate the accumulation of SSIs over time.…”
Section: Comparison With Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Equally, the likelihood of developing an SSI significantly drops after this point. Other studies have identified comparable patterns [2]. So, clearly, redefining the end point will reduce the incidence of SSI.…”
Section: To the Editormentioning
confidence: 75%